Taking Care of Unity at St. Albertus Catholic Senior High School Malang - Yuliarti, Agnes Pradini; Warsono, Warsono; Sarmini, Sarmini (The Indonesian Journal of Social Studies, 2022)
This study aims to explore the representation of multicultural values contained in the school activities This study uses the perspective of James A. Banks multicultural education to identify multicultural values, while Peter L. Berger’s theory of Social Construction to focus on how multicultural values are represented through school activities as an effort to nurture diversity. The analysis in this study used the case study research method of Robert K. Yin. The results of this (1) representation of multiculual values in St. Albertus Catholic High School Malang, among others: tolerance, mutual respect and coexistence. (2) The multicultural values shall be represented through school activities shaded by the student and Pastoral Care departments as well as religious and ethical learning. Knowledge of multicultural values and the implementation of school activities based on the Carmel Spirituality Principle can practically be used as a school effort to implement multicultural policies in order to care for the bestiality at St Albertus Catholic High School Malang